2008
DOI: 10.1128/jb.01006-07
|View full text |Cite
|
Sign up to set email alerts
|

Two RecA Protein Types That Mediate Different Modes of Hyperrecombination

Abstract: RecAX53 is a chimeric variant of the Escherichia coli RecA protein (RecAEc) that contains a part of the central domain of Pseudomonas aeruginosa RecA (RecAPa), encompassing a region that differs from RecAEc at 12 amino acid positions. Like RecAPa, this chimera exhibits hyperrecombination activity in E. coli cells, increasing the frequency of recombination exchanges per DNA unit length (FRE). RecAX53 confers the largest increase in FRE observed to date. The contrasting properties of RecAX53 and RecAPa are manif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 37 publications
0
14
0
4
Order By: Relevance
“…E. coli RecA was purified from the strain JC10289 with the relevant genotype recA thr‐1 leu‐6 Str r [32] carrying the wild type recA gene under its own promoter within the plasmid pUC19‐recA1.1 [33]. The cells were grown at 37 °C in 2 l of Luria–Bertani medium in the presence of 100 μg/ml ampicillin to an OD 595 of 0.6 and the protein expression was induced for 3 h by the addition of nalidixic acid (50 μg/ml).…”
Section: Methodsmentioning
confidence: 99%
“…E. coli RecA was purified from the strain JC10289 with the relevant genotype recA thr‐1 leu‐6 Str r [32] carrying the wild type recA gene under its own promoter within the plasmid pUC19‐recA1.1 [33]. The cells were grown at 37 °C in 2 l of Luria–Bertani medium in the presence of 100 μg/ml ampicillin to an OD 595 of 0.6 and the protein expression was induced for 3 h by the addition of nalidixic acid (50 μg/ml).…”
Section: Methodsmentioning
confidence: 99%
“…Measurement of FRE to assess elevated or depressed levels of recombination in vivo has been developed over the past 15 years (Namsaraev et al ., 1998; Bakhlanova et al ., 2001; Chervyakova et al ., 2001; Lanzov, 2002; Baitin et al ., 2003; 2006; 2008; Lanzov et al ., 2003). The method has the advantage that it can detect essentially all types of genetic exchanges that might occur during conjugation (Baitin et al ., 2008). The method is somewhat more laborious than the convenient and robust method developed by Konrad (Konrad, 1977).…”
Section: Resultsmentioning
confidence: 99%
“…It is also not clear to what extent recombination potential reflects RecA protein structure itself, the modulation of RecA protein function by other factors or the activities of entirely different recombination proteins. Therefore, to directly address the affects of these variables on the in vivo function of RecA, we took advantage of a quantitative genetic analysis of the linkage of donor markers following bacterial conjugation by determining the frequency of recombination exchanges per DNA unit length (FRE) (Namsaraev et al ., 1998; Bakhlanova et al ., 2001; Chervyakova et al ., 2001; Lanzov, 2002; Baitin et al ., 2003; 2006; 2008; Lanzov et al ., 2003). These methods have shown that RecA from E. coli (EcRecA) has a relatively moderate recombinase activity in vivo (Namsaraev et al ., 1998; Lanzov et al ., 2003; Baitin et al ., 2006; 2008), although the activity is presumably optimal for this bacterium.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The protein RecA of pathogenic Pseudomonas aeruginosa (RecAPa), for example, exhibits hyperrecombination increasing FRE by six to seven times, and the hybrid protein RecAX53, the central domain of which consists of 12 amino acids from RecAPa, while the rest consists of 340 amino acids from RecAEc, increases FRE by nine times (Bakhlanova et al, 2001). In contrast to RecAEc, the RecAPa and RecAX53 proteins have, however, an increased biochemical activity that influ ences the recombination rate (Baitin et al, 2008).…”
Section: Introductionmentioning
confidence: 99%